2014
DOI: 10.1038/ncomms4326
|View full text |Cite
|
Sign up to set email alerts
|

The origin of segmentation motor activity in the intestine

Abstract: The segmentation motor activity of the gut that facilitates absorption of nutrients, was first described in the late 19th century but the fundamental mechanisms underlying it remain poorly understood. The dominant theory suggests alternate excitation and inhibition from the enteric nervous system. Here we demonstrate that typical segmentation can occur after total nerve blockade. The segmentation motor pattern emerges when the amplitude of the dominant pacemaker, the slow wave generated by ICC associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 44 publications
4
141
0
Order By: Relevance
“…Strain gauges showed propulsive contractions that changed into stationary contractions after intravenous injection of neurotensin. Using spatio-temporal mapping, we showed that the segmentation motor pattern in the mouse intestine has a checkered appearance, 35 identical to that described by Cannon. 42 Segmentation in the small intestine is caused by interactions of 2 pacemaker activities.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Strain gauges showed propulsive contractions that changed into stationary contractions after intravenous injection of neurotensin. Using spatio-temporal mapping, we showed that the segmentation motor pattern in the mouse intestine has a checkered appearance, 35 identical to that described by Cannon. 42 Segmentation in the small intestine is caused by interactions of 2 pacemaker activities.…”
Section: Discussionmentioning
confidence: 52%
“…In the small intestine, the classical segmentation motor activity is generated when the ICC associated with the deep muscular plexus (ICC-DMP) produce a stimulus-dependent rhythmic electrical activity. 34,35 In the rat colon, it is the ICC-MP that generates a stimulus-dependent low frequency activity; the laboratories of Jimenez in the rat 31 and Takaki in the mouse 36 showed that ICC-MP are associated with a low frequency pacemaker that can drive contractions at frequencies from 0.3 to 2 cpm, 19,21,22,[31][32][33] hence the on/off pattern observed in the present study is likely to be associated with pacemaking from the ICC-MP. It is not known where the ultra-slow pacemaker that drives the slow propagating segmental contractions is located; it may be within the ENS or in the intramuscular ICC (ICC-IM).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…110,111 Also, our understanding of myogenic and other mesenchymal control elements present in the gut wall, has improved based on imaging results. For example, recent reports show that interstitial cells of Cajal can operate independently from enteric neurons to control segmentation motor activity, 112 and need the Ca 2+ -activated Cl − channel Ano1 to coordinate slow waves in the smooth muscle. 113 Another recent study used Oregon Green BAPTA-2 as a Ca 2+ indicator to investigate the involvement of platelet derived growth factor receptor  (PDGFR + ) cells in inhibitory neurostransmission to smooth muscle cells.…”
Section: Live Imaging Of Cellular Activity In the Adult Gutmentioning
confidence: 99%